The Effect of Institutional Ownership, Company Size, Research And Development (R&D) on Extent Intellectual Capital Disclosure: Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Riset And Development (R&D) Terhadap Extent Intellectual Capital Disclosure - Nourma Ninil Alfariza; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the Effect of Institutional Ownership, Company Size, Research And Development (R&D) on Extent Intellectual Capital Disclosure (Studies on High IC Intensive manufacturing companies listed on the IDX in 2015-2018). The sampling method used is purposive sampling method. The number of companies sampled in this study are 12 High IC Intensive Manufacturing Companies Listed on the IDX for the 2015-2018 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that institutional ownership has an effect on Extent Intellectual Capital Disclosure. Firm size has an effect on Extent Intellectual Capital Disclosure. Influential R&D Extent Intellectual Capital Disclosure. Institutional ownership, company size, research and development affect the Extent Intellectual Capital Disclosure.